One-pot synthesis of pyrazoles from sulfonyl hydrazides and alkynyl ketones using environmentally benign sulfonium iodate (I) reagent - Mishra, Akanksha; Talukdar, Mrinal; Krishna, Gamidi Rama; Begari, Eeshwaraiah (ChemistrySelect, 2024)
Pyrazole is an omnipresent moiety in many natural products and pharmaceutically active compounds. Here, we have developed a simple and dynamic method for one-pot synthesis of substituted pyrazoles through the intramolecular cyclization of hydrazides and alkynyl ketones, using a novel sulfonium saltbased iodate (& Iukcy;) reagent system. This method has the advantage that it proceeds in a one-pot, without isolating a less stable hydrazone intermediate. Hypervalent iodine-based reagents are an environmentally benign and greener option to toxic metal oxidants; they have an extensive application in metal-catalyst-free reactions, and this reaction proceeds in less time with high yields.
Keywords: Deprotonation; One-pot reaction; Oxidative iodination; Pyrazole; S(N)2-type cyclization